Improving The Community Economy Through The Empowerment Of Patchouli Oil Farmer Groups In Cempa Village, Aceh Tamiang - Mutia Sumarni; Ikhwan , Ihsanul; Iskandar , Darwisy Nurul; Irhamsyah , Ikhsan; Rambe, Khairunnisa; Hisan, Khairtun; Ulya , Zikritul; Eliza , Zulfa; Mastura (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
Through community economic empowerment, farmer groups in improving the economy of the community in Cempa Village through patchouli oil which is not only a high-value natural product, but also a natural miracle that supports local economic empowerment and sustainability. This research uses a descriptive method, the type of data used is skin, the data sources used are primary and secondary data while the data collection techniques used in the study are observation, interviews, and documentation studies. It is hoped that the results of community empowerment will help farmer groups in improving prosperity by strengthening brand identity, seizing market opportunities, and committing to sustainability so that Cempa Village towards greater global recognition so that ultimately helping the community of Cempa Village farmer groups create opportunities and start their own businesses and become financially independent.